HbE Level and Red Cell Parameters in Heterozygous HbE With and Without α0-Thalassemia Trait - Sakorn Pornprasert (2018)
© 2018 Indian Society of Hematology and Blood Transfusion We compared hemoglobin (Hb) E levels and red cell parameters between heterozygous HbE with and without α 0 -thalassemia trait and also determine their appropriated cut-off points for differentiating these two groups. High performance liquid chromatography analysis results and mean levels of red blood cell (RBC) parameters, including RBC count, total Hb, hematocrit, MCV, MCH and MCHC of heterozygous HbE with α 0 -thalassemia trait (n = 183) and without α 0 -thalassemia trait (n = 1437) were reviewed and compared. The α 0 -thalassemia status in these samples was detected by real-time PCR with SYBR Green1 and high resolution melting analysis. Mean levels of HbE, total Hb, MCV, MCH and MCHC of heterozygous HbE with α 0 -thalassemia trait were significantly lower than those of heterozygous HbE without α 0 -thalassemia trait (P < 0.001). In addition, HbE level at a cut-off value of < 24% was superior to MCV ( < 80 fL) and MCH ( < 27 pg) for differentiating the heterozygous HbE with and without α 0 -thalassemia trait with 100% sensitivity and 87.2% specificity. Despite certain limitations of this study like missing RDW and reticulocyte counts, and not testing for α + -thalassemia and Hb Constant Spring, we conclude that the HbE level at a cut-off point of < 24% is a useful marker for initial discrimination between heterozygous HbE with and without α 0 -thalassemia trait.